2005
DOI: 10.1021/ja0514545
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxyquinoline-N-oxides:  A New Class of “Super” Photoacids1

Abstract: N-Oxidation of hydroxyquinolines leads to a dramatic increase in their excited-state acidity. Time-resolved and steady-state emission characterization of 6-hydroxyquinoline-N-oxide and 2-methyl-6-hydroxyquinoline-N-oxide reveals a rich but less complex proton-transfer behavior than that of its parent hydroxyquinoline. The electronic effect of the oxidized heterocyclic nitrogen atom makes the excited state both less basic and more acidic than the parent and adds hydroxyquinoline N-oxides to the class of high-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 82 publications
2
54
0
Order By: Relevance
“…However, some key molecular processes of proton transfer via hydrogen-bonded wire in biological protein have remained poorly understand so far due to the complex environment, such as the green fluorescent protein (GFP) [32]. Hence, studying on hydrogen-bonding dynamics in the excited-state multiple proton transfer (ESMPT) via hydrogen-bonded wire becomes one of the most popular topics in nowadays, which is very useful for biological investigations [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some key molecular processes of proton transfer via hydrogen-bonded wire in biological protein have remained poorly understand so far due to the complex environment, such as the green fluorescent protein (GFP) [32]. Hence, studying on hydrogen-bonding dynamics in the excited-state multiple proton transfer (ESMPT) via hydrogen-bonded wire becomes one of the most popular topics in nowadays, which is very useful for biological investigations [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…And the resulting ketonic form (8KQ) is supposed to be barely emissive [35]. On the other hand, the hydrogen-bonded wire can be hardly formed in 6-hydroxyquinoline (6HQ) [37][38][39], which requires an extreme long bridge to connect the functional groups. We believe that, the hydrogen-bonded wire with two or three components (H 2 O, NH 3 or alcohols, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Hydroxyquinolines, especially, have been the subject of several studies and their excited state dynamics has been found to be governed by intersystem crossing ͑ISC͒ in organic solvents and ground and excited state proton transfers in aqueous solutions and in ammonia clusters. [4][5][6] However, only few preliminary reports on the fluorescence properties of aminoquinolines exist, [7][8][9][10] even though their biological importance is well recognized. 11,12 Our interest in aminoquinolines is primarily due to their structural features, which have the potential of having severe implications on their photophysical properties and applications thereof.…”
Section: Introductionmentioning
confidence: 99%
“…In the same manner, the tripeptide glycyl-glycyl-glycine (13c) reacted both in DMF and in aqueous DMSO solution with OSu-ester 11 to the peptide linked carbostyril 13c in 54-56% yield. Aminoglucose (14) gave with 11 in 54 % yield the glucose-linked carbostyril 15.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis of 6-quinolinyloxy-acetate 8 in aqueous-ethanolic sodium hydroxide gave in good yields 6-quinolinyloxy-acetic acid 9 which yielded the desired compound 11 after reaction with N-hydroxysuccinimide/diisopropylcarbodiimide in dry tetrahydrofurane. (14) Linkage of fluorescent dyes with biopolymers such as proteins or polysaccharides is a method used for many purposes; e.g. refs [4b,4i,11b,12], and was already successfully applied with similar N1-linked carbostyrils [5].…”
Section: Resultsmentioning
confidence: 99%